Implementasi Pendidikan Karakter Dalam Proses Pembelajaran Matematika Kelas X MA Ma’arif Roudlotut Tholibin Kota Metro - Rahmawati, Ira; Anwar, M Saidun; Saputra, Andika Ari; Fauza, M. Ruskhan (Jurnal Penelitian Tindakan Kelas, 2023)
Character education is very important for nation building to become a dignified generation. So that students can apply character values ​​in everyday life, mathematics is taught through integrating character education values ​​into the learning process. The purpose of this research is to describe and analyze how character education is integrated into mathematics learning at MA Ma'arif Roudlotut Tholib during the 2023/2024 academic year. This type of research is field research with research subjects of school principals, mathematics teachers, and students using descriptive and analytical research methods. Observation, interview, and documentation are the methods used to collect data. While data reduction, data presentation, and drawing conclusions are used in data analysis techniques. The results showed that class X students of MA Ma'arif Roudlotut Tholibin received character education in learning mathematics, as evidenced by the inculcation of a number of character values ​​when learning took place both in class and outside the classroom. In addition, there were several obstacles found regarding differences in student characteristics, such as the lack of motivation in students, the lack of available school facilities, and the low level of time discipline. Thus the solution to these obstacles is to accustom students to applying character values ​​by setting real examples, giving warnings to those who violate them, building character through posters that are affixed to school walls such as banners or slogans that show character values ​​and complete facilities. adequate schools in order to form character education values ​​during the process of cultivating character values ​​in schools.